2022
DOI: 10.3389/fnmol.2022.842674
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Modulates the Spontaneous Activity and Functional Connectivity of Calcarine in Patients With Chronic Stable Angina Pectoris

Abstract: BackgroundAcupuncture is an effective adjunctive therapy for chronic stable angina pectoris (CSAP), while the underlying mechanism is unclear. This study aimed to investigate the central pathophysiology of CSAP and explore the mechanism of different acupoint prescriptions for CSAP from the perspective of brain-heart interaction.MethodsThirty-seven CSAP patients and sixty-five healthy subjects (HS) were enrolled, and thirty CSAP patients were divided into two acupoint prescriptions groups (Group A: acupoints on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…A large number of studies have shown that acupuncture treatment of stable angina has significant effect. [1,7,8] It is necessary to summarize the criteria for acupoint selection and prescription based on the complex compatibility of acupoints to provide theoretical direction for future clinical practice. [9,10] Neurophysiology has proven that organ function is regulated by the corresponding spinal ganglion segment.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that acupuncture treatment of stable angina has significant effect. [1,7,8] It is necessary to summarize the criteria for acupoint selection and prescription based on the complex compatibility of acupoints to provide theoretical direction for future clinical practice. [9,10] Neurophysiology has proven that organ function is regulated by the corresponding spinal ganglion segment.…”
Section: Introductionmentioning
confidence: 99%